Divieti e limiti, processuali e negoziali, applicati ai milites nel Tardo impero - Costa, Darjn A.N. (Cultura giuridica e diritto vivente, 2020)
[Prohibitions and procedural and negotiating limits applied to the milites in the late Empire] The members of the militiae of Rome were always, in various ways, the object of benefits and privileges, for the service provided, but also of prohibitions and limitations. In this essay we investigate, in particular, the prohibition for miles in service to be appointed cognitor or procurator, analyzing, in particular, the imperial legislation in the late Antiquity researching the possible reasons that were at the basis.